Equalising the Income of Municipalities as a Precondition of their Sustainable Development? - Kańduła, Sławomira (Studia Oeconomica Posnaniensia, 2017)
Sustainable local development can be funded with municipalities' own fiscal revenues. However, municipalities vary in terms of their income generating capacities, so their own revenues and expenditures on their own tasks per capita also differ significantly. Excessive differences between local self-government units have a negative impact on the sustainable development of a country. Therefore, state authorities can establish a fiscal equalization mechanism. A study of municipalities in the Wielkopolska region proved that the general subsidy reduces the discrepancies in the revenues of municipalities by over 60% and thus increases the possibility of municipalities financing the tasks undertaken in order to actualize the idea of sustainable local development.